2022
DOI: 10.1123/jsep.2022-0196
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime Stressor Exposure and Psychophysiological Reactivity and Habituation to Repeated Acute Social Stressors

Abstract: This study addressed whether lifetime stressor exposure was associated with psychophysiological reactivity and habituation to a novel laboratory-based stressor. Eighty-six participants (Mage = 23.31 years, SD = 4.94) reported their exposure to lifetime non-sport and sport-specific stressors before completing two consecutive trials of the Trier Social Stress Test, while cardiovascular (i.e., heart rate) and endocrine (i.e., salivary cortisol) data were recorded. Exposure to a moderate number of lifetime non-spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Additional research is also needed to investigate the role of early-life and lifetime exposure to major stressors, especially interpersonal stressors, given that such stressors are associated with the age of menarche ( Natsuaki et al, 2009 ), and as such, the age of HC use onset, as well as psychological and biological stress reactivity ( Giletta et al, 2017 ; McLoughlin et al, 2022 ; Slavich et al, 2023 ). In addition, as the present study only included women using first-through-third generation oral HCs, and only investigated differences in effects based upon generation of HC used (see Supplemental Materials for generational analyses), future research would benefit from investigating how the androgenicity of the progestin used in different HCs impacts women’s stress responses, along with the dosage of synthetic hormones contained in the HC method, the method of HC administration, a women’s duration of HC use, how timing of administration of HCs pills in relation to stressor exposure impact stress responses, and the genomic mechanisms through which HC use impacts women’s stress responses.…”
Section: Discussionmentioning
confidence: 99%
“…Additional research is also needed to investigate the role of early-life and lifetime exposure to major stressors, especially interpersonal stressors, given that such stressors are associated with the age of menarche ( Natsuaki et al, 2009 ), and as such, the age of HC use onset, as well as psychological and biological stress reactivity ( Giletta et al, 2017 ; McLoughlin et al, 2022 ; Slavich et al, 2023 ). In addition, as the present study only included women using first-through-third generation oral HCs, and only investigated differences in effects based upon generation of HC used (see Supplemental Materials for generational analyses), future research would benefit from investigating how the androgenicity of the progestin used in different HCs impacts women’s stress responses, along with the dosage of synthetic hormones contained in the HC method, the method of HC administration, a women’s duration of HC use, how timing of administration of HCs pills in relation to stressor exposure impact stress responses, and the genomic mechanisms through which HC use impacts women’s stress responses.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that stressor exposure disproportionately affects populations based on several factors, including socioeconomic status (SES), marital status, gender, and race/ethnicity (Armstrong et al, 2018). Reactions to such stressors also vary across individuals (Giletta et al, 2018; McLoughlin et al, 2022; Quinn et al, 2020). From the perspective of coping theory (Lazarus & Folkman, 1984), for example, individuals with lower SES, such as lower income (Adler et al, 1994) or education (Ross & Wu, 1995), are more prone to adopting unhealthy behaviors, such as substance abuse (Wills et al, 1998) and to engage in risky sexual behaviors (Hillis et al, 2001).…”
Section: Introductionmentioning
confidence: 99%